2020
DOI: 10.3389/fmars.2020.00217
|View full text |Cite
|
Sign up to set email alerts
|

Marine Aquaculture Impacts on Marine Biota in Oligotrophic Environments of the Mediterranean Sea – A Review

Abstract: The potential impacts of marine aquaculture are reviewed, focusing both on smallscale local effects near the farm environment and a broad spatial scale that impacts a number of different ecosystem components. Local changes in productivity, biodiversity, and behavioral changes of wild fauna affected by nearby farm habitats were examined. Global aquaculture trends of growth perspectives as related to seafood supply, impacts on wild stock and biodiversity depletion, genetic changes in wild fish populations due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 75 publications
0
17
1
1
Order By: Relevance
“…It is not just about scheduling and executing dive operations to repair or replace buoys, nets, moorings, structural lines, connection nodes or anchors as each incident can totally or partially affect the cage structures and, therefore, the life that is contained within them [ 5 , 6 ]. For example, the breakage of a mooring line or the loss of a buoy can lead to the deformation of the supporting cage [ 7 ]; the volume of the cage is then reduced and the welfare of the population inside the cage is substantially diminished to the point of causing heart attacks among the individuals in the population due to high stress [ 8 , 9 ]. Another example is an open or broken net: wildlife can still enter the cage but the contained individuals can also escape to freedom.…”
Section: Introductionmentioning
confidence: 99%
“…It is not just about scheduling and executing dive operations to repair or replace buoys, nets, moorings, structural lines, connection nodes or anchors as each incident can totally or partially affect the cage structures and, therefore, the life that is contained within them [ 5 , 6 ]. For example, the breakage of a mooring line or the loss of a buoy can lead to the deformation of the supporting cage [ 7 ]; the volume of the cage is then reduced and the welfare of the population inside the cage is substantially diminished to the point of causing heart attacks among the individuals in the population due to high stress [ 8 , 9 ]. Another example is an open or broken net: wildlife can still enter the cage but the contained individuals can also escape to freedom.…”
Section: Introductionmentioning
confidence: 99%
“…Mariculture has substantial impacts on ecosystem health and sustainable use. Along with the unprecedented and continuous expansion, China's mariculture industry has been received many undesirable environmental and ecological impacts in terms of seawater eutrophication (Islam, 2005), chemical's accumulation (Burridge et al, 2010;Liu et al, 2017), microplastic pollution (Chen et al, 2021), habitat destruction (Ahmed and Thompson 2018;Ottinger et al, 2016), biodiversity depletion (Ticina et al, 2020), and space competition between fish farmers and other marine stakeholders (Bostock et al, 2010). However, many peer experts such as Tang (2019) and Jiao (2018) suggested that mariculture can deliver a broad range of ecosystem services functions, and many unexpected environmental effects of mariculture can be alleviated even eliminated by the integration of advanced ecosystem approaches and appropriate management.…”
Section: Introductionmentioning
confidence: 99%
“…Information on the cage culture in Xuan Dai Bay, Van Phong Bay and Cam Ranh Bay is presented in Table 1. However, aquaculture, similarly to many other agricultural sectors, is known to have several negative impacts on the environment and natural resources [4][5][6][7][8], especially in coastal waters [4][5][6][7][8]. These impacts could be chemical accumulations (e.g., heavy metals, antifouling biocides, aquaculture medicinal products, polycyclic aromatic hydrocarbons, and warfare agents by anthropogenic inputs) [9][10][11][12][13][14][15], nutrient loads [8,11,12,16,17], organic matter deposited in sediment [11,12,18], and habitat destruction [8,19,20] as well as negative interaction of invasive species with wild fish [21,22].…”
Section: Introductionmentioning
confidence: 99%